Evaluation of a gamification methodology in higher education - Lopes, Rui Pedro (2017)
The gamification neologism is applied to using game-thinking and game mechanics to solve problems and to engage audiences. In the previous year we applied the concept in the context of the Higher Education, in the course of computer science. We used several game design mechanisms in several aspects of the learning process. A reward mechanism was central to the gamification approach, providing automatic classification of students and constant and up-to-date feedback of their progress within the course. Each chapter of the course’s content was mapped to a level, in a total of five. The student had to complete all the levels to be able to succeed in the course. Each level provided three difficult levels, which the student could choose and, according to this choice, adopt a classification grade.